Simulation research on dynamic characteristics of scroll compressor with flexible clearance. - Haifei Qiu; Zhang Yifan; Li Feiyang; Chen Xiandong (PLoS ONE)
The scroll compressor is a rotating machinery with high-speed and high-precision characteristics. In this paper, a vector model of the kinematic pair was constructed based on two-state clearance. To confirm the adverse effects of tiny clearance (0<r≤0.1mm) on the scroll compressor, a dynamics simulation of the spindle was performed under flexible contact conditions with different clearances. The study indicates that simulation results for flexible and rigid bodies are vastly different, and the former is closer to reality. Compared with the case in an ideal state (0mm), clearance at 0.01mm and 0.04mm can cause an enormous impact on the critical bearing components of the spindle, such as the orbiting scroll, cross-slip ring, and support bearing, which results in unexpected vibration and noise. However, when the clearance increases to 0.07mm and 0.1mm, the collision amplitude and friction resistance inside the needle bearing are relatively small, which avoids violent impacts on the machine. This paper considers the effect of spindle flexibility and transmission clearance simultaneously, which helps to explore the running mechanism of a scroll compressor with clearance.